2022
DOI: 10.3389/fneur.2022.1026609
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparison of commercial artificial intelligence solutions for detection of large vessel occlusion at a comprehensive stroke center

Abstract: PurposeDespite the availability of commercial artificial intelligence (AI) tools for large vessel occlusion (LVO) detection, there is paucity of data comparing traditional machine learning and deep learning solutions in a real-world setting. The purpose of this study is to compare and validate the performance of two AI-based tools (RAPID LVO and CINA LVO) for LVO detection.Materials and methodsThis was a retrospective, single center study performed at a comprehensive stroke center from December 2020 to June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…The high specificity of 93 % for the anterior circulation was similar to that shown in previous studies [10] , [11] , [12] . For the few observed false positives by the CINA® LVO software, a visible reason for the incorrect assessment could, in most cases, be deducted from the images included in the software’s report (for example two cases of partly thrombosed aneurysms and one case with a sharp M2 vessel curve marked as occlusions).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The high specificity of 93 % for the anterior circulation was similar to that shown in previous studies [10] , [11] , [12] . For the few observed false positives by the CINA® LVO software, a visible reason for the incorrect assessment could, in most cases, be deducted from the images included in the software’s report (for example two cases of partly thrombosed aneurysms and one case with a sharp M2 vessel curve marked as occlusions).…”
Section: Discussionsupporting
confidence: 90%
“…McClouth et al [10] found a sensitivity and specificity for overall LVO detection (including ICA, M1 and M2) to be 98 % and 98 %, respectively. In a third study, by Schlossman et al [12] , the analysis also indicated an uneven performance with a sensitivity of 55 % for LVO detection in the ICA and 87 % for M1 occlusions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Over the last few years, multiple studies have evaluated the performance of LVO detection for several available software packages with varying results. Sensitivities ranged from 73–98% and specificities ranged from 52–98% [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. As a reference standard, in one study, neuroradiologists’ ability to detect anterior LVO using CTA and NCCT had sensitivities ranging from 75 to 88% and specificities ranging from 88 to 97% [ 37 ].…”
Section: Ischemic Strokementioning
confidence: 99%
“…In contrast to other studies, posterior circulation and cervical ICA occlusions were included in the analysis. Just as it is for radiologists, AI-based algorithms have low sensitivity for detection of distal occlusions (i.e., M2 or M3) [ 31 , 33 , 35 ].…”
Section: Ischemic Strokementioning
confidence: 99%